High stromal transforming growth factor β–induced expression is a novel marker of progression and poor prognosis in gastric cancer. Issue 6 (9th September 2018) - Suzuki, Masaki; Yokobori, Takehiko; Gombodorj, Navchaa; Yashiro, Masakazu; Turtoi, Andrei; Handa, Tadashi; Ogata, Kyoichi; Oyama, Tetsunari; Shirabe, Ken; Kuwano, Hiroyuki
Abstract : Background and Objectives: Transforming growth factor β‐induced (TGFBI) protein is a secreted extracellular matrix protein with conflicting roles in cancer, acting as a tumour suppressor and a promoter, which appears to be tissue specific. The role of TGFBI in gastric cancer (GC) remains unclear, which we aimed to investigate using the clinical samples as well as an in vitro coculture model of GC. Methods: The clinical significance of TGFBI was assessed in 208 GC samples using immunohistochemistry. Molecular function of TGFBI in the GC cells was examined by small interfering RNA‐mediated TGFBI downregulation in the gastric fibroblasts cocultured with the GC cells. Results: TGFBI expression was localised mainly in the cancer stroma and not in the noncancerous gastric tissue or the GC cells. High TGFBI expression was significantly associated with poor prognosis and cancer progression. Downregulation of TGFBI in the cocultured gastric fibroblasts inhibited the invasion and migration abilities of the GC cells. Conclusions: High stromal TGFBI expression might be a useful predictive marker for poor prognosis in GC patients. Furthermore, TGFBI in the cancer stromal cells is a promising target for GC treatment.